Serum Adiponectin Level in Diabetic Patients with and without Helicobacter pylori Infection: Is There Any Difference? - Jamshid Vafaeimanesh; Akram Heidari; Marzieh Effatpanah; Mahmoud Parham (The Scientific World Journal)
Background. Increased insulin resistance is an extragastrointestinal manifestation of Helicobacter pylori (HP) infection. HP changes the level of inflammatory markers and cytokines and changes the adipocyte function by altering the adiponectin level. Given the high prevalence of HP and diabetes in our society, we evaluated the association between HP and serum adiponectin level. In this cross-sectional study, 211 diabetic patients under treatment other than insulin were studied. These patients were divided into two groups of HP+ and HP− based on their HP IgG antibody serology and their blood adiponectin levels were measured. Data was analyzed using independent t-test, Chi-square test, and Fisher’s exact test. Results. Seventy-two patients with an average age of 51.56±8.34 years were HP− and 139 patients with an average age of 50.35±9.01 years were HP+. The mean serum adiponectin level in HP− and HP+ groups was 4.54±5.43 and 5.64±3.88 ng/mL, respectively. Insulin resistance degree was significantly higher in HP+ group (HP− = 3.160±3.327 versus HP+ = 4.484±3.781, P=0.013) but no significant difference was found between the mean serum adiponectin level in HP− and HP+ groups (P=0.140). Conclusions. Although the insulin resistance degree was significantly higher in HP+ diabetic patients, no significant relationship was found between HP infection and serum levels of adiponectin.